Bed II Sequence Stratigraphic context of EF-HR and HWK EE archaeological sites, and the Oldowan/Acheulean succession at Olduvai Gorge, Tanzania. Issue 120 (July 2018) - Stanistreet, Ian G.; McHenry, Lindsay J.; Stollhofen, Harald; de la Torre, Ignacio
Abstract: Archaeological excavations at EF-HR and HWK EE allow reassessment of Bed II stratigraphy within the Junction Area and eastern Olduvai Gorge. Application of Sequence Stratigraphic methods provides a time-stratigraphic framework enabling correlation of sedimentary units across facies boundaries, applicable even in those areas where conventional timelines, such as tephrostratigraphic markers, are absent, eroded, or reworked. Sequence Stratigraphically, Bed II subdivides into five major Sequences 1 to 5, all floored by major disconformities that incise deeply into the underlying succession, proving that simple "layer cake" stratigraphy is inappropriate. Previous establishment of the Lemuta Member has invalidated the use of Tuff IIA as the boundary between Lower and Middle Bed II, now redefined at the disconformity between Sequences 2 and 3, a lithostratigraphic contact underlying the succession containing the Lower, Middle, and Upper Augitic Sandstones. HWK EE site records Oldowan technology in the Lower Augitic Sandstone at the base of Sequence 3, within Middle Bed II. We suggest placement of recently reported Acheulean levels at FLK W within the Middle Augitic Sandstone, thus emphasizing that handaxes are yet to be found in earlier stratigraphic units of the Olduvai sequence. This would place a boundary between the Oldowan and Acheulean technologies at Olduvai in the Tuff IIB zone or earliest Middle Augitic Sandstone. A major disconformity between Sequences 3 and 4 at and near EF-HR cuts through the level of Tuff IIC, placing the main Acheulean EF-HR assemblage at the base of Sequence 4, within Upper rather than Middle Bed II. Sequence stratigraphic methods also yield a more highly resolved Bed II stratigraphic framework. Backwall and sidewall surveying of archaeological trenches at EF-HR and HWK EE permits definition of "Lake-parasequences" nested within the major Sequences that record downcutting of disconformities associated with lake regression, then sedimentation associated with lake transgression, capped finally by another erosional disconformity or hiatal paraconformity caused by the next lake withdrawal. On a relative time-scale rather than a vertical metre scale, the resulting Wheeler diagram framework provides a basis for recognizing time-equivalent depositional episodes and the position of time gaps at various scales. Relative timing of archaeological assemblage levels can then be differentiated at a millennial scale within this framework.